Five new species of Phaonia Robineau-Desvoidy (Diptera: Muscidae) from China - Xue, Wanqi; Du, Jing (Zootaxa, 2020)
Five new species of Phaonia are described from China, namely P. sunqiia Xue & Du sp. nov., P. zhangjunyui Xue & Du sp. nov., P. liujiayui Xue sp. nov., P. wangpingga Xue sp. nov. and P. tianmushanensis Xue sp. nov. The available keys to the three species-groups where the new species belong were updated.